1986
DOI: 10.1007/bf01542224
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian mothers and their children: A comparison with solo parent heterosexual mothers and their children

Abstract: Two types of single-parent households and their effects on children ages 3-11 years were compared. One type comprised 50 homosexual mothers and their 56 children, and the other was a group of 40 heterosexual mothers and their 48 children. There were 30 daughters and 26 sons of homosexual mothers and 28 daughters and 20 sons of heterosexual mothers. The sexual identity and social relationships of the children were assessed in relation to the sexual orientation of the mothers. The samples consisted of families f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
154
1
28

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 15 publications
4
154
1
28
Order By: Relevance
“…The negative effects of bullying were amplified when educators provided no support to the victims or even joined in with the homophobic remarks. This is in contrast to other research findings, which suggest that children in same-gendered families are no more likely to experience teasing or bullying than children from any other family (Green, Mandel, Hotvedt, Gray & Smith, 1986;Hare, 1994;Patterson, 1997). Clarke, Kitzinger and Potter (2004) note that reporting any negative aspect such as bullying or teasing provokes a dilemma for same-gender parents, since claims about homophobic bullying are frequently used to undermine same-gender parents.…”
Section: Same-gendered Families and Schools: A Research Overviewcontrasting
confidence: 90%
“…The negative effects of bullying were amplified when educators provided no support to the victims or even joined in with the homophobic remarks. This is in contrast to other research findings, which suggest that children in same-gendered families are no more likely to experience teasing or bullying than children from any other family (Green, Mandel, Hotvedt, Gray & Smith, 1986;Hare, 1994;Patterson, 1997). Clarke, Kitzinger and Potter (2004) note that reporting any negative aspect such as bullying or teasing provokes a dilemma for same-gender parents, since claims about homophobic bullying are frequently used to undermine same-gender parents.…”
Section: Same-gendered Families and Schools: A Research Overviewcontrasting
confidence: 90%
“…8,9 Lesbian mothers fall within the range of normal psychologic functioning on interviews and psychologic assessments and report scores on standardized measures of self-esteem, anxiety, depression, and parenting stress indistinguishable from those reported by heterosexual mothers. 10 Lesbian mothers strongly endorse child-centered attitudes and commitment to their maternal roles [11][12][13] and have been shown to be more concerned with providing male role models for their children than are divorced heterosexual mothers.…”
Section: Parenting Attitudes and Behavior Personality And Adjustmenmentioning
confidence: 99%
“…Several studies comparing children who have a lesbian mother with children who have a heterosexual mother have failed to document any differences between such groups on personality measures, measures of peer group relationships, self-esteem, behavioral difficulties, academic success, or warmth and quality of family relationships. 9,11,15,16,20,21 Children's self-esteem has been shown to be higher among adolescents whose mothers (of any sexual orientation) were in a new partnered relationship after divorce, compared with those whose mothers remained single, and among those who found out at a younger age that their parent was homosexual, compared with those who found out when they were older. 22 Prevalent heterosexism and stigmatization might lead to teasing and embarrassment for children about their parent's sexual orientation or their family constellation and restrict their ability to form and maintain friendships.…”
Section: Children's Emotional and Social Developmentmentioning
confidence: 99%
“…The earliest investigations, which were of children who had been conceived in heterosexual relationships but brought up by lesbian mothers after the parents had divorced or separated, found that mother-child relationships were just as close in lesbian families as they were in postseparation families headed by single heterosexual mothers (Golombok, Spencer, & Rutter, 1983;Green, Mandel, Hotvedt, Gray, & Smith, 1986;Hoeffer, 1981;Kirkpatrick, Smith, & Roy, 1981).…”
Section: Parentingmentioning
confidence: 99%